468PHistological type analysis of 10-year follow-up of WJTOG0105: A phase III study comparing second- and third-generation regimens with concurrent thoracic radiotherapy in unresectable stage III non-small cell lung cancer. (24th November 2019) - Tsuboi, M; Zenke, Y; Chiba, Y; Satouchi, M; Mitsuoka, S; Shimizu, J; Daga, H; Fujimoto, D; Mori, M; Aoki, T; Sawa, T; Omori, S; et al.
Abstract: Background: Third-generation regimens with chemoradiotherapy has been established as one of a standard treatment in the phase III study WJTOG0105 even 10 years after starting treatment. We conducted an additional analysis by the histological type (Non-squamous [Non-Sq] vs. Squamous [Sq]) to examine differences of efficacy and patterns of initial failure. Methods: Patients received the following treatments: MVP, mitomycin (8 mg/m 2 on day 1, 29), vindesine (3 mg/m 2 on day 1, 8, 29, 36), and cisplatin (80 mg/m 2 on day 1, 29) with concurrent TRT (60 Gy), followed by 2 courses of MVP; IC, weekly irinotecan (20 mg/m 2 )/carboplatin (AUC 2) for 6 weeks with concurrent TRT (60 Gy), followed by 2 courses of irinotecan (50 mg/m 2 )/carboplatin (AUC 5); PC, weekly paclitaxel (40 mg/m 2 )/carboplatin (AUC 2) for 6 weeks with concurrent TRT (60 Gy), followed by 2 courses of paclitaxel (200 mg/m 2 )/carboplatin (AUC 5). Overall survival (OS), progression free survival (PFS), and patterns of initial failure were compared by the histological type. Results: From September 2001 to September 2005, 440 patients (arm A, n = 146; arm B arm, n = 147; arm C, n = 147) were enrolled. The median follow-up time 140 months. The median OS and PFS were 23.5, 8.3 months in Non-Sq and 19.7, 8.3 months in Sq. The efficacy of PC and IC was compared with MVP in each histological type. For Non-Sq, the median OS and PFS were 25.1, 8.3 months in PC and 20.3, 8.3 months in IC and 25.2, 8.4 months in MVP. For Sq, the median OS and PFS were 20.5, 9.9 months in PC and 17.1, 7.8 months in IC and 19.4, 8.3 months in MVP. There was no statistically significant difference in OS and PFS between PC, IC and MVP in each histological type. In the patterns of initial failure, out-field recurrence rate in Non-Sq (51.1%) was higher than Sq (26.1%). Furthermore, the patterns of initial failure were similar between PC, IC and MVP. Conclusions: Weekly PC with concurrent TRT showed similar efficacy to MVP with concurrent TRT, with no correlation to the histological type in 10-years follow-up with WJTOG0105. In the pattern of initiated failure, out-field recurrence in Non-Sq was tend to be higher than in Sq. Clinical trial identification: Clinical trial information: 000030811. Legal entity responsible for the study: The authors. Funding: West Japan Oncology Group (WJOG). Disclosure: M. Tsuboi: Honoraria (institution): Bristol-Myers Squibb. M. Satouchi: Honoraria (institution): Bristol-Myers Squibb; Research grant / Funding (institution): Bristol-Myers Squibb. D. Fujimoto: Honoraria (self): Bristol-Myers Squibb. T. Hirashima: Honoraria (self): Bristol-Myers Squibb; Research grant / Funding (institution): Bristol-Myers Squibb. N. Yamamoto: Honoraria (self): Bristol-Myers Squibb; Research grant / Funding (institution): Bristol-Myers Squibb. K. Nakagawa: Honoraria (self): Bristol-Myers Squibb; Research grant / Funding (institution): Bristol-Myers Squibb. All other authors have declared no conflicts of interest.